WOMEN AND THE CRIMINAL QUESTION: A CRIMINOLOGICAL APPROACH - Halima Menani,; Soufyane Badraoui, (International Journal of Innovative Technologies in Social Science, 2025)
Rising female criminality, a less common phenomenon, is sparking criminological interest. There’s a marked contrast in the nature of crimes committed by men and women. Men predominantly engage in violent crimes, robberies, and drug-related activities, while women are more likely to commit less serious offenses, including fraud, pick-pocketing, and economic crimes. These inequalities are partially due to sociocultural elements, such as traditional gender roles and varied criminal opportunities. Criminological study, which initially focused on male delinquency, gradually favored the emergence of feminist criminology as an autonomous discipline. This innovation tackles the roots and forms of female delinquency. Women’s social, economic, and cultural contexts and their relation to crime were studied. This led to a specialized field of gender-aware criminology emerged.